Research Progress on Chemical Constituents, Pharmacological Actions and Application of Codonopsis Radix as Both Medicine and Food - ZHANG Huan, LI Chao, JI Chenfeng (Shipin Kexue, 2024)
Codonopsis Radix, the dried roots of the genus Codonopsis of Platycodonaceae, has a very long history of culinary and medicinal use in China and is considered to strengthen the middle warmer and benefit vital energy as well as to benefit the stomach and help produce saliva in Chinese medicine. Codonopsis Radix contains a rich variety of chemical constituents, including flavonoids, alkaloids, polysaccharides, saponins, steroids, trace elements and amino acids, with many pharmacological effects, such as enhancing immunity, protecting the heart, nerve and gastrointestinal tract, regulating blood sugar, antioxidant, anti-fatigue, antibacterial, anti-virus, and anti-tumor functions, so it has been increasingly applied as both food and medicine. In this article, the chemical composition, pharmacological actions and application of Codonopsis Radix are reviewed so as to provide a reference for understanding the theoretical basis for the health benefits of Codonopsis Radix as well as for its development and application.